TREATMENT OF EUTHYROID GOITTER - Kurbanova , Nozima Sabirdjanovna; Shodieva , M; Samizhanova , M; Rustamova , N (Educational Research in Universal Sciences, 2024)
The article briefly summarizes modern ideas about the pathogenetic therapy of euthyroid goiter. The advantages, disadvantages and potential effectiveness of monotherapy with iodine preparations, suppressive therapy with levothyroxine preparations and combination therapy with iodine and levothyroxine preparations are considered. The principles of postoperative prevention of goiter recurrence are described[8-13].